From Data to Decisions: The Impact of AI on Healthcare Systems - Khan, Murad; Sherani, Abdul Mannan Khan (BULLET : Jurnal Multidisiplin Ilmu, 2024)
Artificial Intelligence (AI) has gradually permeated almost all aspects of healthcare delivery emerging as a critical enabler for continued advancement. Let us investigate literature on AI in the subject domain of healthcare which comprises diagnostics, clinical decision, medicine customization and health care regulation systems. Machine learning deep learning, natural language processing are improving the clinical analytics by improving diagnosis, treatment, and care. Furthermore, also integrally involves AI in activities and tasks that aimed at improving the facility’s operations such as the distribution of resources, patients’ traffic and numerous administrative duties. This paper acknowledges that there is a great potential in the use of AI in the healthcare sector, but there arises important ethical questions around the use of AI such as data ownership, fairness of the algorithm, and fears around transparency and accountability. Remaining issues affecting its growth include regulatory issues since the existing frameworks cannot cope with the emerging AI innovations. The future of adopting AI has potentialities on early detection of diseases and illnesses, discovery of new drugs, tele-medicine, and in the international health sector. AI will help with increasing the availability of healthcare for patients in the regions where the necessary facilities are scarce and advancing the creation of individual treatment plans. But for that to happen, it is important to solve ethical, regulating and data problems connected with AI deployment. The successful implementation of AI in HC has possibilities to achieve better patient outcomes, decrease costs and general advancement of quality and accessibility of HC for everyone in the world.